FRAMING OF NICKEL MINING COVERAGE IN RAJA AMPAT ON TEMPO.CO AND DETIK.COM - Ahmad Arifin (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2026)
The rapid expansion of nickel mining in Indonesia has generated intensifying tensions between the imperatives of natural resource exploitation and the imperatives of preserving ecologically sensitive territories. This study conducts a comparative framing analysis of news coverage concerning nickel mining activities in the Raja Ampat archipelago, focusing on two influential Indonesian online news platforms: Tempo.co and Detik.com. Grounded within a qualitative research paradigm employing a comparative case study design, the investigation applies Robert N. Entman's four-dimensional framing model encompassing problem definition, causal diagnosis, moral evaluation, and treatment recommendation to ten purposively selected news articles published in June 2025. The analytical findings reveal that Detik.com predominantly frames the issue through a techno-administrative lens, accentuating regulatory violations and governmental corrective procedures, whereas Tempo.co consistently adopts a structural-critical orientation that foregrounds concerns relating to legal governance, constitutional principles, and civil society advocacy. These divergent framing tendencies illuminate how editorial orientation actively mediates the construction of environmental discourse within the Indonesian public sphere, confirming that media framing constitutes a constitutive rather than merely reflective dimension of environmental governance controversies.